A Value Based Big Data Maturity Model - Farah, Badie (Journal of Management Policy and Practice, 2017)
Data has the power to change every business and organization. The issue is what data, and what analysis is applied to that data. Data may be looked upon as a store of information useful for answering questions, providing prospective on problems, and shedding light on potential solutions. Because of this potential, organizations and businesses are enticed to acquire, maintain, and process volumes of structured and unstructured data. This paper advances a big data maturity model which is used to describe the standing of an organization with respect to its big data effort, and provide a road map for advancing such an effort. This model is differentiated from others by its orientation toward the value its big data strategy provides to the organization.